Soil Microbial Communities and Enzyme Activities after Long-Term Application of Inorganic and Organic Fertilizers at Different Depths of the Soil Profile - Holík, Ladislav; Hlisnikovský, Lukáš; Honzík, Roman; Trögl, Josef; Burdová, Hana; Popelka, Jan (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2019)
Fertilization is a key factor for sustaining productivity in agroecosystems. A long-term experiment in cambisol following periodical application of several types of fertilization has been running at the experimental site since 1954. In this study, we determined the impact of applied inorganic and/or organic fertilizers on the activity of soil enzymes and on the structure of microorganisms at depths of 0-30 cm and 30-60 cm. Single-factor comparison showed that use of inorganic and/or organic fertilizer had an insignificant e_ect on the activities of soil enzymes (at depths 0-30 cm and 30-60 cm) and also on the structure of microbial communities at both depths studied. Only soil respirations exhibited stimulation by combined fertilization. The results, irrespective of sampling depth (0-60 cm), showed that application of combined organic and inorganic fertilization stimulated the activity of glucosidases and use of inorganic fertilizer inhibited the activity of arylsulphatases. Respirations were stimulated by application of organic fertilizer and combined fertilization. Nevertheless, principal component analyses, which calculate with multidimensional data, revealed di_erences in samples treated by sole mineral fertilizer compared to other variants, especially in the lower layer. In general, our results indicate that use of combined fertilization may improve biological characteristics in deeper parts of soil profile and possibly increase biological activity in agroecosystems.
Keywords: soil microorganisms; phospholipid fatty acids; soil enzyme activities; agricultural soil fertilization